2016
DOI: 10.1002/anie.201511432
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Rhenium Complexes Divert Doxorubicin to the Mitochondria

Abstract: Doxorubicin, a well-established chemotherapeutic agent, is known to accumulate in the cell nucleus. By using ICP-MS, we show that the conjugation of two small organometallic rhenium complexes to this structural motif results in a significant redirection of the conjugates from the nucleus to the mitochondria. Despite this relocation, the two bioconjugates display excellent toxicity toward HeLa cells. In addition, we carried out a preliminarily investigation of aspects of cytotoxicity and present evidence that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 33 publications
3
68
0
Order By: Relevance
“…The mitochondria‐targeting effect of MMCNs is additionally corroborated by inductively coupled plasma atomic emission spectrometer (ICP‐AES), since the presence of Fe elements in MMCNs allows sensitive quantification of the metal content in the cellular compartments after subtracting the baseline Fe levels in different organelles of untreated cells . Remarkably, the Fe quantification evidences a significant accumulation of MMCNs in the mitochondria (Table S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
“…The mitochondria‐targeting effect of MMCNs is additionally corroborated by inductively coupled plasma atomic emission spectrometer (ICP‐AES), since the presence of Fe elements in MMCNs allows sensitive quantification of the metal content in the cellular compartments after subtracting the baseline Fe levels in different organelles of untreated cells . Remarkably, the Fe quantification evidences a significant accumulation of MMCNs in the mitochondria (Table S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 85%
“…[12][13][14][15] Certain members of this class of compounds exhibit potent cytotoxic activity,w hich can be leveragedf or their use as anticancer agents. [16][17][18][19][20][21][22][23] Here, we describe our investigation of an ew rhenium(I) tricarbonyl complexb earing ac helating polypyridyl liganda nd an axial isonitrile ligand as ap otent anticancer agent.O ur efforts to understand the mechanismo f actiono ft his tricarbonyl rhenium isonitrile polypyridyl (TRIP) complex ( Figure 1) have revealed that it is an effective ER stress-inducing agent with significant antiproliferativeactivity. TRIP was synthesized by treating the previously reported complex [Re(CO) 3 (dmphen)OTf] with excess para-tolyl isonitrile in tetrahydrofuran.…”
mentioning
confidence: 99%
“…[21] A variety of fluorescent agents, including quantum dots (QDs), [22] organometallic compounds, [23] fluorescent proteins (FPs), [24] organic dyes, [25] and so on, have been developed and used in mitochondrial dynamism tracking and monitoring. It utilizes fluorescent agents to label mitochondria with real-time operation, non-invasive testing and cost-effective performance.…”
Section: Introductionmentioning
confidence: 99%